IMPROVING STUDENTS’ WRITING ABILITY THROUGH QUICK WRITING STRATEGY TO THE ELEVENTH GRADERS OF SMA MUHAMMADIYAH PAGARALAM - M. Bambang Purwanto; Evi Agustina Sari; Tiur Simanjuntak (Esteem Journal of English Education Study Programme, 2022)
Writing is one of the most difficult skills to be mastered by students and most of students did not have enough ability to write, in order to solve this problem the writer used one of strategy which is quick writing. The main objective of this study was to identify whether or not the use of Quick Writing strategy was effective to enhance the student writing ability. The population was Eleventh grade students of SMA Muhammadiyah Pagaralam. In taking the sample, the researcher used purposive sampling. Sixty students, involved as a participants in this study. The research design used quasi experimental. The data were collected by using writing test. The data were analyzed by using paired sample t-test and independent sample t-test. The value t-obtain was (4.765) at the significant level 0.000. Since the value of t-obtained was higher than critical value of t-table (2.001). The result showed that there was significant difference between the students who were taught by using Quick writing strategy and those were not. In short, the students who were taught by using Quick writing strategy had better improvement in their writing ability. It was effective to use quick writing strategy